PENGARUH ETOS KERJA DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA DAPUR COKELAT GALAXY (PT. ABISETYA ALKA ARYAGUNA) - Wahyu Andri Wibowo; Ida Bagus Alit Ksama P; I Putu Ajie Windu Kertayoga; Risna Haryati; Ni luh Sri Kasih (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This study aims to examine the effect of: (1) work ethic and career development on employee performance, (2) work ethic on employee performance, (3) career development on employee performance. The research design used in this study is causal quantitative research. In this study, the research subjects were employees who worked at Dapur Cokelat Galaxy (PT. Abisetya Alka Aryaguna) and the object of research is work ethic, career development and employee performance. The population taken in this study were 83 employees at Dapur Cokelat Galaxy (PT. Abisetya Alka Aryaguna), so the overall sample was 45 people. Data were collected by interviews, document recording and questionnaire methods, then analyzed by multiple regression analysis. The results showed that: (1) work ethic and career development have a significant effect on employee performance, (2) work ethic has a significant effect on employee performance, (3) career development has a significant effect on employee performance.